Transvaginal Sonographic Imaging and Associated Techniques for Diagnosis of Ovarian, Deep Endometriosis, and Adenomyosis: A Comprehensive Review - Aas-Eng, Mee Kristine; Montanari, Eliana; Lieng, Marit; Keckstein, Joerg; Hudelist, Gernot (Seminars in Reproductive Medicine, 2020)
Imaging of endometriosis and in particular deep endometriosis (DE) is crucial in the clinical management of women facing this debilitating condition. Transvaginal sonography (TVS) is the first-line imaging method and magnetic resonance imaging (MRI) may provide supplemental information. However, the delay in diagnosis of up to 10 years and more is of concern. This problem might be overcome by simple steps using imaging with emphasis on TVS and referral to tertiary care. Finally, TVS is crucial in mapping extent and location of disease in planning surgical therapy and counseling women regarding various therapeutic options. This review presents the available data on imaging of endometriosis with a focus on TVS and MRI for DE, adenomyosis, and ovarian endometriomas including endometriomas in pregnancy as well as the use of “soft markers.” The review presents an approach that is in accordance with the International Deep Endometriosis Analysis (IDEA) group consensus statement.
Keywords: deep endometriosis; transvaginal sonography; magnetic resonance imaging; imaging method